Pengujian Efikasi Skala Laboratorium Kayu Hasil Fumigasi Terhadap Serangan Rayap Tanah (Coptotermes curvignathus) - Imam Wahyudi; Istie Sekartining Rahayu; . Arinana (Institut Pertanian Bogor, 2014)
Fumigated wood was assumed to retain durability level against wood destroying factors. Due to lack of data, fumigated wood durability against wood destroying factors needs to be investigated, especially toward subterranean termites. The aim of this research was to evaluate fumigated wood durability against subterranean termites attack in laboratory scale (ASTM D 3345-2008). Wood samples used were sengon (Falcataria moluccana), rubberwood (Hevea brasiliensis), and mangium (Acacia mangium). Samples of 2.5 × 2.5 × 0.6 cm were fumigated inside 2 × 1 × 1 m of fumigation chamber using 2, 4, 6, 8, and 10 liters of ammonia solution for 4 days. The samples were then transferred into glass bottle, along with sterile sand and 200 worker and 20 soldier subterranean termites. After 4 weeks, mortality and weight loss percentage were measured. All treatments showed 100% of mortality, while a significant decline in weight loss percentage was varied depends on wood species as well as the volume of ammonia. Therefore, fumigated wood was proven resistant against the attacks of subterranean termites.